The economic evaluation of vocational training programs - Zymelman, Manuel; World Bank. (Baltimore : Published for the World Bank by Johns Hopkins University Press, 1976)
The study presents an evaluation on the different types of training in developed and developing countries.
Includes bibliographical references: p. 117-122.
obn 23/01/2019
Loans
Keywords: Vocational education; Education - economic aspect